Soil fertility stratification in a fragile ecosystem: Depth-wise gradients of nitrogen, phosphorus, potassium and pH in Chure hills Nepal - Neupane, Nija; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2025)
The Chure region of Nepal, an ecologically fragile landscape, faces severe degradation, threatening its soil fertility and ecosystem services. Conducted in 2024, this study aimed to assess the vertical and spatial variations of key soil fertility indicators, total nitrogen (TN), available phosphorus (AP), available potassium (AK), and pH, in the forest soils of this understudied region. Soil samples were collected from 29 permanent sample plots across six districts (Bara, Parsa, Rautahat, Mahottari, Sarlahi, Siraha) in Madhesh Province. Stratified random sampling was employed to collect samples from three depth intervals (0–10, 10–20, and 20–30 cm). TN was determined using the Kjeldahl method, AP by Olsen’s method, AK by flame photometry, and pH using a digital pH meter. A two-way ANOVA tested the main effects of depth and district (p< 0.05). The results revealed significant vertical gradients for all parameters. TN decreased markedly with depth (0.034% at 0–10 cm to 0.012% at 20–30 cm), while AP, AK, and pH increased significantly with depth. This subsoil enrichment is attributed to the region’s specific pedogenic processes, including leaching in coarse-textured soils, fixation in alkaline subsoils, and weathering of the calcareous/sandstone parent material. Spatially, Rautahat district consistently exhibited the highest levels of TN (0.034%), AP (106.46 kg/ha), AK (20.67 kg/ha), and pH (7.69). In contrast,Siraha had the lowest AP (99.84 kg/ha), AK (19.38 kg/ha), and pH (7.21), and Mahottari had the lowest TN (0.010%). These findings provide a critical scientific baseline for designing targeted soil conservation, sustainable forest management, and land rehabilitation strategies in this vulnerable ecosystem.